2002
DOI: 10.1007/s00134-002-1380-9
|View full text |Cite
|
Sign up to set email alerts
|

Diprivan attenuates the cytotoxicity of nitric oxide in cultured human bronchial epithelial cells

Abstract: Diprivan effectively attenuates the cytotoxicity of excessive NO exposure in IB-3 cells at concentrations that are clinically attainable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Alzheimer's disease (AD) is the most common cause for dementia and its prevalence continues to rise in ageing societies (1). Histologically, AD is characterized by pathological b-amyloid plaques and neurofibrillary tau deposits (2)(3)(4). In vivo characterization of corresponding imaging biomarkers have been strengthened in a currently published research framework (5).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is the most common cause for dementia and its prevalence continues to rise in ageing societies (1). Histologically, AD is characterized by pathological b-amyloid plaques and neurofibrillary tau deposits (2)(3)(4). In vivo characterization of corresponding imaging biomarkers have been strengthened in a currently published research framework (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, the phases of dementia must be identified for an accurate diagnosis. Ten to sixteen percent of people with MCI rapidly progress to AD per year [16], making it a severely impaired stage compared to AD. Stabilization or reversal to the healthy stage in MCI patients is extremely varied [33].…”
Section: Introductionmentioning
confidence: 99%
“…These disturbances are increased in conditions of hyperoxia and may lead to cell death. [1][2][3] Recently, it has been reported that anesthetic agents may offer some protection against such lesions induced by IR, and hence knowledge of the mechanisms involved may provide anesthesiologists with strategies to lower morbidity and improve patient survival. 4 Propofol, a highly lipid soluble hypnotic agent, has proven antioxidant activity in both in vitro and in vivo studies; this is based on the fact that its chemical structure is similar to that of a natural antioxidant: i.e., vitamin E. [5][6][7] In this sense, several studies have demonstrated that propofol acts as a scavenger of oxygen free radicals, decreasing lipid peroxidation and increasing the antioxidant capacity of erythrocytes and other tissues in organs such as liver, kidney, heart and lung.…”
mentioning
confidence: 99%